Pharmacovigilance of antiretroviral dolutegravir in the state of Paraná - Bárbara Thaís Poliselo de Sá; Frederico Alves Dias; Flavia Helen Correia; Doroteia Aparecida Höfelmann; Yanna Dantas Rattmann (Universidade Estadual de Maringá, 2022)
The aim of this study was to investigate adverse reactions to Dolutegravir, a drug recently made available by the Unified Health System (SUS) for treating HIV infections. The frequency, severity and sex distribution of adverse reactions to Dolutegravir were identified over the first 18 months of its availability in users in the state of Paraná. Information was obtained through the pharmacovigilance questionnaire prepared by the Ministry of Health, accessed through the Logistics Control System for Medicines (SICLOM). During the study period, dolutegravir was dispensed to 9,865 patients in the state. However, 9,207 users (93.3%) answered the pharmacovigilance questionnaire. Among them, 1.75% reported 279 adverse reactions. This population was composed mainly of male people (69.57%), in the ratio of 2.29 men for each woman, white (67.08%), aged between 20 and 29 years (26.71%), single (45.34%) and with education between 8 and 11 years of study (41.61%). Gastrointestinal (36.92%) and nervous system (14.34%) disorders were the most prevalent. 77.78% adverse reactions were considered non-serious by users. It can be concluded that dolutegravir had a low prevalence of adverse reactions in users in the state of Paraná, demonstrating to be safe for use by the population in therapy against HIV, in accordance with clinical trials